The evaluation of JAK inhibitors on effect and safety in alopecia areata: a systematic review and meta-analysis of 2018 patients - Mei-qi Mao; Yu-xin Ding; Jing Jing; Zhen-wei Tang; Yu-jie Miao; Xiao-shuang Yang; Yu-hong Chen; Sheng-zhao Chen; Xian-jie Wu; Zhong-fa Lu (Frontiers in Immunology, 2023)
BackgroundJAK inhibitors treat various autoimmune diseases, but an updated systematic review in treating alopecia areata is currently lacking.ObjectiveEvaluate the specific efficacy and safety of JAK inhibitors in alopecia areata by systematic review and meta-analysis.MethodsEligible studies in PubMed, Embase, Web of Science, and Clinical Trials up to May 30, 2022, were searched. We enrolled in randomized controlled trials and observational studies of applying JAK inhibitors in alopecia areata.Results6 randomized controlled trials with 1455 patients exhibited SALT50 (odd ratio [OR], 5.08; 95% confidence interval [CI], 3.49-7.38), SALT90 (OR, 7.40; 95% CI, 4.34-12.67) and change in SALT score (weighted mean difference [WSD], 5.55; 95% CI, 2.60-8.50) compared to the placebo. The proportion of 26 observational studies with 563 patients of SALT5 was 0.71(95% CI, 0.65-0.78), SALT50 was 0.54(95% CI 0.46-0.63), SALT90 was 0.33(95% CI, 0.24-0.42), and SALT score (WSD, -2.18; 95% CI, -3.12 to -1.23) compared with baseline. Any adverse effects occurred in 921 of 1508 patients; a total of 30 patients discontinued the trial owing to adverse reactions.LimitationsFew randomized controlled trials met the inclusion criteria and insufficiency of eligible data.ConclusionJAK inhibitors are effective in alopecia areata, although associated with an increased risk.